Is there a Future After Doha? European Trade Strategies in Perspective - Hübner, Kurt (Eurostudia, 2007)
AbstractAgriculture definitely is at the top of developmental issues that must be solved if there is to be a future beyond Doha. A new global trade regime, however, needs to go beyond agriculture and deal with the pressing issues of a global economy characterized by unevenness and inequality. Such an agenda would have to simultaneously address the re-establishing of the principle of multilateralism that is endangered not only by regional agreements but also by the desire of non-governmental organizations fighting for labour and environmental standards.